2010
DOI: 10.1186/1746-1596-5-54
|View full text |Cite
|
Sign up to set email alerts
|

Significance of lobular intraepithelial neoplasia at margins of breast conservation specimens: a report of 38 cases and literature review

Abstract: BackgroundPresence of lobular intraepithelial neoplasia (LIN) is not routinely reported as part of margin assessment in breast conservation therapy (BCT) as in ductal carcinoma in situ (DCIS). With new emerging evidence of LIN as possible precursor lesion, the hypothesis is that LIN at the margin may increase the risk of local recurrence with BCT. The aim is to determine whether there is an increase incidence of recurrence when LIN is found at surgical margins on BCT.MethodsWe retrospectively reviewed a total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 19 publications
(16 reference statements)
0
6
0
Order By: Relevance
“…Also, it is the rst time that such an electrical diagnoser would be applied as an intra-operative margin detection approach in clinics. Here, after recording and calibrating hypoxia based margin diagnosis on 258 fresh breast samples had been resected from 74 patients, quanti ed diagnostic scorings of CDP response peaks were de ned in correlation with their permanent histopathology results based on world health organization (WHO) classi cation of breast tumors [10], [11], [12], [13] that proposed for CDP scores. This diagnostic approach was veri ed by clinical trials on 188 patients undergone BCS/mastectomy surgeries.…”
Section: Introductionmentioning
confidence: 99%
“…Also, it is the rst time that such an electrical diagnoser would be applied as an intra-operative margin detection approach in clinics. Here, after recording and calibrating hypoxia based margin diagnosis on 258 fresh breast samples had been resected from 74 patients, quanti ed diagnostic scorings of CDP response peaks were de ned in correlation with their permanent histopathology results based on world health organization (WHO) classi cation of breast tumors [10], [11], [12], [13] that proposed for CDP scores. This diagnostic approach was veri ed by clinical trials on 188 patients undergone BCS/mastectomy surgeries.…”
Section: Introductionmentioning
confidence: 99%
“…This guideline was based on a few studies in which the presence of LCIS at the resection margin did not affect subsequent local recurrence [ 8 9 ]. However, another study reported that LCIS or atypical lobular hyperplasia at the margin was significantly associated with increased local recurrence [ 10 ]. The latter study reported a recurrence rate of 39% in the positive margin group compared with a recurrence rate of just 7.9% in the negative control group.…”
Section: Discussionmentioning
confidence: 99%
“…Samples consisted of ADH with more than two foci, DCIS and IDCs most often showed peak currents higher than 203µA, while others consisted of one focus of ADH, UDH, and FCC lesions showed peak currents lower than 196µA. Hence, the responses of CDP are classifiable based on the newest edition of ductal intraepithelial neoplasia (DIN) [10], lobular intraepithelial neoplasia (LIN) [11], and fibroepithelial lesion (FEL) [12] systems reported by the world health organization (WHO) [13]. Most abnormal samples were found in DIN classification (as the most occurred types of breast diseases such as IDC, DCIS, ADH, and UDH).…”
Section: Pathological Classification Of Cdp Responses On In-vitro Breast Samplesmentioning
confidence: 99%
“…It is the first time that such an electrical diagnoser would be applied as a real-time cancer detector in live tissues. Here, after recording and calibrating hypoxia based margin diagnosis on 258 fresh breast tumor samples, quantified diagnostic scorings of CDP response peaks were defined in correlation with their permanent histopathology results based on the world health organization (WHO) classification of breast tumors [10], [11], [12], [13]. This diagnostic approach showed more than 95% sensitivity in its best calibration, which shed new light for application as a surgeon assistant in the future after passing clinical trials.…”
Section: Introductionmentioning
confidence: 99%